Radical-Scavenging Activity and Ferric Reducing Ability of Juniperus thurifera (L.), J. oxycedrus (L.), J. phoenicea (L.) and Tetraclinis articulata (L.) - Meryem El Jemli; Rabie Kamal; Ilias Marmouzi; Asmae Zerrouki; Yahia Cherrah; Katim Alaoui (Hindawi Limited, 2016)
Objective. The aim of this work is to study and compare the antioxidant properties and phenolic contents of aqueous leaf extracts of Juniperus thurifera, Juniperus oxycedrus, Juniperus Phoenicea, and Tetraclinis articulata from Morocco. Methods. Antioxidant activities of the extracts were evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical-scavenging ability, Trolox equivalent antioxidant capacity (TEAC), and ferric reducing antioxidant power (FRAP) assays. Also the total phenolic and flavonoids contents of the extracts were determined spectrophotometrically. Results. All the extracts showed interesting antioxidant activities compared to the standard antioxidants (butylated hydroxytoluene (BHT), quercetin, and Trolox). The aqueous extract of Juniperus oxycedrus showed the highest antioxidant activity as measured by DPPH, TEAC, and FRAP assays with IC50 values of 17.91±0.37 μg/mL, 19.80±0.55 μg/mL, and 24.23±0.07 μg/mL, respectively. The strong correlation observed between antioxidant capacities and their total phenolic contents indicated that phenolic compounds were a major contributor to antioxidant properties of these plants extracts. Conclusion. These results suggest that the aqueous extracts of Juniperus thurifera, Juniperus oxycedrus, Juniperus phoenicea, and Tetraclinis articulata can constitute a promising new source of natural compounds with antioxidants ability.